2017
DOI: 10.1063/1.4994042
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependence of magnetoelectric coefficient in BaTiO3/CoFe2O4

Abstract: Using the three-dimensional space coordinate transformation approach, orientation dependence of the longitudinal magnetoelectric coefficient αE33 in tetragonal BaTiO3/face centered cubic (fcc) CoFe2O4 composites was calculated in arbitrary directions. A clamp-free condition is used in the calculation. The direction along which αE33 is maximum is a function of psij, pεij, dij of piezoelectric phase and msij, mμij, qij of magnetostrictive phase referred to the crystallographic coordinate system. For a fixed CoFe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…BT is a high piezoelectric material with intrinsic dipoles in the BT lattice. [ 34,35 ] The piezoelectric mechanism of BT can be understood that intrinsic dipoles in BT are aligned upon poling and stretched/squeezed upon compression/the reversed force to the BT lattice). [ 34,35 ] The decrease at f BTF ≈ 15–25% may be due to a deteriorated film structure at high filler loadings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BT is a high piezoelectric material with intrinsic dipoles in the BT lattice. [ 34,35 ] The piezoelectric mechanism of BT can be understood that intrinsic dipoles in BT are aligned upon poling and stretched/squeezed upon compression/the reversed force to the BT lattice). [ 34,35 ] The decrease at f BTF ≈ 15–25% may be due to a deteriorated film structure at high filler loadings.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34,35 ] The piezoelectric mechanism of BT can be understood that intrinsic dipoles in BT are aligned upon poling and stretched/squeezed upon compression/the reversed force to the BT lattice). [ 34,35 ] The decrease at f BTF ≈ 15–25% may be due to a deteriorated film structure at high filler loadings. As shown in Figure S3 (Supporting Information), pores increase in the composites with filler loading at high BTFs loadings, which may result in decreased performances of the PENG.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to that reported for the BTO−CFO system, wherein it was suggested that the shape anisotropy of the tetragonal-structured BTO is essential for giving rise to the crystalline orientation dependence of the magnetoelectric coupling observed in the bilayer BTO−CFO system. 61 It is apparent that controllability of the crystal shape anisotropy and orientation of CFO mesocrystals can provide additional handles for manipulating the magnetic properties, which is important for practical applications such as bitpatterned media wherein the magnetic anisotropy of CFO mesocrystal served as a medium to store bit information. 17 Thus, we believe that our findings can pave an alternative avenue for investigating the largely unexplored feasibility assessments in utilizing the engineered CFO mesocrystals for bit-patterned media applications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Matrices of elastic stiffnesses c ij and piezoelectric constants d ij are presented in [6 × 6] and [3 × 6] rank tensors, respectively. According to Euler’s rotation laws, physical quantity matrices in a new orientation are obtained by two-step product operations with transformation matrices A , N , and M [21,22].…”
Section: Methodsmentioning
confidence: 99%